Determination of salivary flow rate, pH, and dental caries during pregnancy: A study - Amruta A Karnik; Sandeep S Pagare; Vasavi Krishnamurthy; Sonal P Vahanwala; Mandavi Waghmare (Wolters Kluwer Medknow Publications, 2015)
Introduction: Saliva is an important diagnostic biofluid and the salivary composition is affected by various systemic conditions including pregnancy. Aims: The study was conducted to evaluate the salivary flow rate and pH in pregnant and non-pregnant Indian women and, consequently, to compare and correlate the salivary flow rate, pH, and prevalence of dental caries in both groups. Settings and Design: A cross-sectional study was conducted in our institute on a sample of 30 pregnant and 30 non-pregnant women. Materials and Methods: The clinical findings for Decayed-Missing-Filled Teeth (DMFT) index were recorded. Unstimulated whole saliva was collected to determine the salivary flow rate and pH. Statistical Analysis Used: Data were statistically analyzed using Student's t-test. Results: Salivary flow rate was lower in pregnant women (0.63 ml/min) as compared to that in non-pregnant women (0.81 ml/min) (P < 0.05) and the pH was also lesser in pregnant women (6.56) than in non-pregnant women (6.86) (P < 0.05). DMFT index showed a strong negative correlation with pH in pregnant women and non-pregnant women (P < 0.05). Conclusion: A difference was observed between the salivary parameters of pregnant and non-pregnant women in this sample. However, all the values were within the normal range. A significant inverse relation was found between salivary pH and dental caries for both the groups.